POLA KOMUNIKASI DINAS PARIWISATA PEMERINTAH DAERAH KABUPATEN BANYUWANGI DALAM MENGEMBANGKAN POTENSI PARIWISATA MELALUI KEGIATAN FESTIVAL - Hery Bambang Cahyono (MEDIAKOM : Jurnal Ilmu Komunikasi, 2018)
Banyuwangi was once just the easternmost district in East Java Province. This district is famous as an area that has the science of black magic, which is a very deadly black science. But now appear skyrocketed into a tourist area that is very amazing. Many tourism potentials are developed, there are also many tourist visits and ultimately can increase the dignity and economy of the community. This study wanted to find out the effective cooperation pattern of the Banyuwangi Regional Government Tourism Office in developing tourism potential through festival activities, the media used and the obstacles faced. The research method used is descriptive qualitative. The theory used is the theory of social exchange.The results showed that the pattern of effective cooperation was carried out by the Department of Tourism by internally dividing tasks with all local government task units related to festival activities, while externally cooperating with all communities, especially cultural communities. Furthermore, the Tourism Office also promotes through internet media, print media, and interpersonal communication media. The results of this study also indicate that the obstacles faced the dilemma between the effort to develop tourism potential and the teachings of Islam, the low mastery of public information technology and the divided support between the people in the south and the people in the north towards cultural products as a tourism potential. Keywords: Banyuwangi, Communication, Tourism